HYPOPLASIA OF THE FACIAL ARTERY SUBSTITUTED BY TRANSVERSE FACIAL ARTERY - N. Yotova; S. Novakov; A. Fasova; P. Timonov (Trakia Journal of Sciences)
PURPOSE. The facial artery is one of the main arteries which supply the face with blood. The different types have been researched not only for anatomical purposes but also to facilitate the different medical specialties. METHODS AND RESULTS. Our team found an unusual case of a facial artery with smaller lumen. The region, which it supplies, is partially substituted by the transverse facial artery. In the observed course the facial artery had a considerably smaller caliber than usual. After it appears on the surface of the face it divides into two untypical branches - anterior and superior. Contrariwise the transverse facial artery has a significantly bigger lumen. The separate branches, which usually originate from the facial artery, here arise from the aforementioned artery. CONCLUSIONS. These types of anatomical variations are very important for muscle and skin flaps in plastic surgery of the face. Every deviation from the normal anatomy of the main blood vessels can also lead to errors in invasive surgery procedures and medical imaging. The vascularization of the face and its variations is subject for many different disciplines.